Influence of hydroquinone content on thermotropic liquid crystalline copolymers and nanocomposites: thermo-mechanical properties and morphology. Issue 15 (22nd March 2022) - Woo, Hyeonjun; Jeon, Hara; Jang, Du Chan; Kwac, Lee Ku; Kim, Hong Gun; Chang, Jin-Hae
Abstract : Thermotropic liquid crystalline copolyesters (Co-TLCPs) were synthesized by varying the hydroquinone (HQ) molar ratio from 1–5 with respect to the 2, 5-diethoxyterephthalic acid (ETA) monomer. Abstract : Thermotropic liquid crystalline copolyesters (Co-TLCPs) were synthesized by varying the hydroquinone (HQ) molar ratio from 1–5 with respect to the 2, 5-diethoxyterephthalic acid (ETA) monomer. The thermal properties and liquid crystalline mesophases of the synthesized Co-TLCP were investigated. All of the Co-TLCPs synthesized using a HQ molar ratio of 1–5 showed a nematic liquid crystalline phase. Among the Co-TLCPs obtained using HQ in various molar ratios, the most stable physical properties and a clear liquid crystalline phase were obtained when HQ was 4 mol. Among the various Co-TLCPs synthesized, hybrids were prepared using Co-TLCP synthesized with a 1 : 4 = ETA : HQ ratio and organoclay. A 1–10% loading of the organoclay Cloisite 93A was employed per weight of TLCP, and the clay was dispersed using the melt intercalation method. Among the Co-TLCP hybrids, the morphology and thermal properties of the hybrids were investigated according to the changes in the Cloisite 93A in the 1–10 wt% range. In general, the thermal properties were superior when the organoclay loading was 3 wt% and were inferior when the organoclay amount was 5 wt% or more. This result was confirmed by the dispersibility of the clay through transmission electron microscopy.